Rational bidding meets emotional viewing: the landscape of English auction livestreams in the age of algorithms - Li, Siqi; Mohd Nor Akmal Khalid; Iida, Hiroyuki (Penerbit Universiti Kebangsaan Malaysia, 2024)
English auctions, renowned for their blend of economic and entertainment elements, serve as dynamic platforms for selling goods. This research, grounded in Game Refinement Theory and the Motion in Mind Model, delves into bidder behavior to elucidate its impact on entertainment perceptions at varying levels of rationality. Our findings uncover distinct patterns of behavior across completely irrational, partially rational, and fully rational bidders, highlighting how these differences influence the entertainment value. Specifically, we examine participants' bidding frequency, proficiency in information gathering, enforcement of beliefs, and rationality, all of which are perceived differently by viewers of live-streamed auctions. The study significantly deepens our understanding of English auctions' psychological and strategic foundations. It gives auction organizers crucial insights into enhancing economic and entertainment outcomes, emphasizing the strategic importance of timing and patience in bidding. This multifaceted approach not only underscores the economic indicators such as price dynamics and bidder competition but also integrates social and psychological perspectives, revealing how social interactions and cognitive processes influence auction dynamics and participant behavior. Such insights are invaluable for designing auctions that are both economically efficient and engaging, ensuring a balanced experience for all participants.